Ingegneri & Ingegneria a Firenze A quarant'anni dall'istituzione della Facoltà di Ingegneria - Corvi, Andrea; FROSALI, GIOVANNI; PARIS, ENIO; Pelosi, Giuseppe; Viviani, Alessandro (Firenze University Press, 2013)
The initial idea for this volume was born while rethinking the organisation of the University of Florence following the recent reform, with the aim of retracing the evolution of the Faculty of Engineering throughout its 40 years, telling and documenting its history, collecting memories and documents from a period characterised by significant changes. The research carried out by the curators and many colleagues has progressively broadened the horizon of the work to collect not only the contents of the academic history but also those of the "civil" history of the Faculty, observing its laborious growth, affirmation and consolidation in the Florentine University, and also noting the relationships with the social and economic context (the city, the region, the national and international involvement) that surrounds a significant collective entity such as "our" Faculty of Engineering. This made it possible to explore and document relevant areas that are fundamental for a non-trivial knowledge of how many actors have crossed the scenario of the Faculty and of which phenomena the Faculty itself has been an observer and protagonist. Thus, the work has been enriched with a great number of contents, declined in each chapter with pleasant energy and that are difficult to summarise in a purely historical or celebratory paradigm. If we try and visualise the readers of this volume, we think of those who will find there the path of their life, who will there find the roots of the present and who will want to discover the reasons for the future.